PENGARUH IKLAN MEDIA SOSIAL DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE (Survei pada Followers Instagram Sataka Watch) - Lomri, Dzikry Nurzamil (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2023)
This study aims to obtain an overview and influence of social media advertising and brand image on online purchasing decisions. This research uses descriptive and verification methods with a quantitative approach. The population in this study amounted to 10,434 with a sample of 200 respondents who were consumers of Sataka Watch using a proposive sampling technique. The data were processed statistically using the Structural Equation Modeling (SEM) method. The findings in this study found that the description of social media advertising, brand image and online purchase decisions were in a fairly good category. Social media advertising and brand image have a positive and significant influence on online purchasing decisions. These findings indicate that the implementation of social media advertising and brand image by Sataka Watch will drive purchasing decisions for Sataka Watch online.